Interior design preferences of middle-income Filipino millennials when booking their staycations via Airbnb - Del Rosario, Ruwayna Alqaseer (College of Home Economics, University of the Philippines Diliman, 2023)
This study sought to determine the interior design preferences of middle-income Filipino millennials when booking staycations via Airbnb using mixed-method research design which combines both qualitative and quantitative methods. Respondents were chosen purposively through a set of criteria being (1) Filipino millennials or individuals belonging to the age group of 27 - 42 years old, (2) middle-income earner as defined by the Bureau of Internal Revenue, and (3) must have booked Airbnb rental within Pampanga. An online survey questionnaire was used as the data gathering tool for all I 09 respondents who were invited using snowball sampling via social media. An in-depth interview that included photo-assessments of actual Airbnb listings in Pampanga was later conducted with six (6) selected respondents via Zoom. Through thematic and descriptive analysis, the survey and the in-depth interview results were assessed using three main considerations, namely: 1) demographics, 2) current living conditions, and 3) purpose of booking. Aside from those three factors mentioned, the Onion Theory of Comfort and the Sense of Place Theory were also used to support further analysis. It was revealed that I) budget, 2) convenience and flexibility, and 3) overall interior style are the main motivations that drive the respondents' preferences. Findings suggest that respondents prefer 1) Modern-Contemporary Style, followed by 2) Minimalist-Japanese Style, while 3) Rustic-Industrial and Tropical-Balinese tied in 3rd place. In terms of interior characteristics, data suggests that 1) hygiene and sanitation ranked first in the respondents' priorities, followed by 2) safety and security, and 3) overall interior design. Other findings suggest that preferences in interior characteristics vary depending on the respondents' demographics and purpose of booking. The researcher recommends future similar studies to come up with an improved questionnaire that provides more visual cues and reader-friendly descriptions about interior design styles for Airbnb to avoid confusion.